Factors affecting knowledge, attitude, and practice of COVID-19: A study among undergraduate university students in Bangladesh - Mufti Nadimul Quamar Ahmed; Shamim Al Aziz Lalin; Saeed Ahmad (Taylor & Francis Group, 2023)
The global expansion of the COVID-19 outbreak is one of the worst disasters the world has faced in recent decades. This study explored various factors of knowledge, attitude, and practice regarding COVID-19 among Bangladeshi undergraduate university students. In addition, we also look at how COVID-19 based knowledge, attitude, and practice influence each other. Using a random sampling technique and a self-administered structured questionnaire survey, this study collected data from 167 private university students in Bangladesh from 1st October to 30th October 2020. Data were analyzed using descriptive statistics (including frequencies, percentages, and means), binary logistic regression, bivariate regression analysis, and factor analysis. The findings suggest that most of the students learned about COVID-19 from various sources, including news media (TV, radio, newspapers, etc.), international organizations (WHO, UN, etc.), various government programs, or from their friends, family members, or neighbors. Most of the students were concerned about becoming sick, keeping social distance, and family members' job insecurity, followed by the university shutdown and the subsequent quarantine. Many students believe Bangladesh's media, government, medical sector, and religious organizations played a significant role during COVID-19. Binary logistic regression demonstrates that students' gender, department, and residency significantly explained their COVID-19 knowledge. In addition, students' attitudes significantly vary with their religion and place of residence. Students' departments and semesters found significant in explaining their practice regarding COVID-19. Moreover, factor analysis results also identified several crucial factors in explaining students' overall knowledge, attitude, and practice of COVID-19. Finally, we found a statistically significant relationship between knowledge, attitude, and practice.